Proposing a waqf based ijarah smart sukuk model for development of waqf properties - Hassan, Rusni; Khan, M.B; Ghafoorzai, S. A.; Ali, Jawwad; Damkar, Shehbaz (Springer Nature, 2022)
This paper focuses on presenting a working model by combining the concepts ofWaqf and smart Sukuk thatworks under the contract of Ijarah. Therefore, it can be referred to as a waqf based Ijarah Smart Sukuk model. In a study conducted by Che Zuina Ismail (2015), it is found that due to several reasons such as bureaucracy and lack of transparency inwaqf administration,Waqf has lost much of its dynamism. Due to these reasons and several others, many waqf properties are either lying idle or in a dilapidated condition, which has led to Awqaf’s effectiveness and role being questioned. There is a need to broadly advertise the significant role played by Awqaf as an instrument of social welfare. Hence, this model is suggested for the development of waqf properties and to revive the role of Waqf in society’s social well-being. By using the qualitative method, this paper also highlights the issues or challenges involved in the practical application of the smart Sukuk or Ijarah contract, including possible Shari’ah issues. The paper’s policy implication suggests that the states adopt this technologically advanced and Shari’ah compliant working model to target the development-related issues of waqf properties. This paper will also offer the existing and upcoming professionals in Islamic finance a broader perspective about smart Sukuk and hopefully encourages them to develop a favourable framework for smart Sukuk and other smart contracts, which is currently lacking.